Capital goods export to developing economies: implication from exporter’s level of technology and destination country’s threat of imitation - Rozilee Asid,; Noor Aini Khalifah,; Abu Hassan Shaari Md.Nor,; Tamat Sarmidi, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This article estimates the trade effect of capital goods exports from 19 OECD into 57 developing and emerging economies trade partners for the period 1990 to 2010. The impact of capital goods exports from the OECD countries is assessed using panel gravity model analysis. We examine the possibility of market-power or market-expansion related to capital goods export into the trading partners hypothesized using the intellectual property right (IPR) index, level of exporters’ technology and imitation threats in the destination country. Our empirical result shows some consistencies on the evidence of market-expansion effect towards capital goods exports which is directly observed from both exporters’ level of technology and destination country’s IPR protection level. Indirectly, a diminishing effect on market expansion is observed when conditioned on one interacting variable. We also predict a consistent market-power effect observed from threat of imitation over time.